Cultivating Critical Thinking Skills in Early Childhood through Inquiry-Based Learning Models Grounded in Teachers' Experiences - Rosidah, Siti; Zulaeha, Ida; Formen, Ali (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study aims to describe the implementation of inquiry-based learning models, grounded in teachers' teaching experiences, to enhance critical thinking skills in early childhood at RA Nurul Haq and TKIT Umar Bin Khatab Kudus. Using a qualitative descriptive approach with a case study model, the research investigates the processes and outcomes of inquiry-based learning. Data were collected through observations, interviews, and document reviews, focusing on children aged 4-6. Results indicate that the inquiry-based learning model significantly enhances children's critical thinking skills when applied by certified and experienced teachers. This model promotes balanced cognitive, affective, and psychomotor development through systematic exploration and problem-solving activities. However, challenges persist for non-certified teachers due to limited training. The study's implications are substantial for early childhood education, as implementing an inquiry-based learning model can improve critical thinking skills essential for children's academic and personal growth. It prepares them to face 21st-century challenges such as critical thinking, creativity, communication, and collaboration. Limitations include the study's focus on a specific demographic and the disparity in training and certification levels among teachers, highlighting the need for comprehensive professional development programs. Future research should expand the scope to include a broader range of educational settings, investigate the long-term effects of inquiry-based learning on critical thinking skills, and explore integrating inquiry-based models with other teaching strategies to maximize their effectiveness. In conclusion, this study underscores the positive impact of an inquiry-based learning model, grounded in teachers' teaching experiences, on enhancing critical thinking skills in early childhood education.